Potensi Dan Pengembangan Umkm Madu Lokal Trigona Sp. Di Desa Lengkongjaya, Kecamatan Cigalontang, Kabupaten Tasikmalaya - R. Arif Malik Ramadhan; Habib Jidni Fauzan; Dita Rahmananda; Dika Safa Nurullita; Tazki Nurul Ilahiah; Ranti Destin; Riza Ahmad Sulaeman; Yussar Nurfahman (Universitas Perjuangan Tasikmalaya, 2026)
This community empowerment program focused on the cultivation of Trigona bees and the development of a local honey-based micro-enterprise in Lengkongjaya Village, Cigalontang District, Tasikmalaya Regency. The program aimed to enhance community capacity in stingless bee cultivation, product processing and packaging, as well as digital marketing to strengthen the competitiveness of “Madu Kampung Pramuka”. Activities included field observations, interviews, focus group discussions, technical training on sustainable beekeeping, branding and packaging assistance, and digital marketing education. The results indicated significant improvement in farmers’ knowledge regarding eco-friendly bee cultivation, promotional content creation, and the use of social media and e-commerce platforms. The honey products were packaged more attractively and marketed through digital platforms. The program also fostered ecological awareness, particularly the importance of maintaining flowering vegetation as bee forage. Social and economic benefits included increased household income, stronger village identity as a Honey Village, and enhanced community collaboration. Overall, trigona-based honey enterprise development effectively supports local economic resilience while promoting environmental sustainability through an eco-entrepreneurship approach.